Analisis dan Perancangan Sistem Manajemen Klaim Berbasis Web dan Aplikasi Blackberry® - Bayu Kanigoro; Andy Wijaya; C. N. Firmana; Astari Jusman (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Web and mobile technology help a lot of business activities since it can be accessed from the Internet and intranet networks so that flow of the information needed can reach out various locations. Web and mobile technology combined with E-CRM technology like helpdesk can be used to improve services. This study aims to design a web-based claim management system (supported with helpdesk system) and its BlackBerry® application for PT. Hoppecke Indonesia. An analysis through literature study and field survey (interview to the employees of PT. Hoppecke Indonesia) is implemented in this study based on the incremental method. The result achieved is a design web-based claims management system and the BlackBerry® application. The design is expected to maintain the relationship between customers and companies, especially in term of item maintenance and to make easy for customers to obtain information that will lead to loyalty to the company. Plus, the documentation of each interaction between customer and the company can be recorded properly.